3
$\begingroup$

I am trying to solve the problem no. 41(i) on page $33$, Higher Algebra by Barnard and Child.

The problem statement is:

If $ax^5+bx^2+c$ has a factor of the form $x^2+px+1$, prove that $$(a^2-c^2)(a^2-c^2+bc)=a^2b^2.$$

By synthetic division, I have found the remainder of $ax^5+bx^2+c$ upon division by $x^2+px+1$ is $$(ap^4-3ap^2-bp+a) x +(ap^3-2ap-b+c).$$

As $x^2+px+1$ is a factor of $ax^5+bx^2+c$, the memainder must be indentically zero. That is:\begin{align*} ap^4-3ap^2-bp+a&=0 \tag{1}\\ ap^3-2ap-b+c&=0 \tag{2} \end{align*} Then subtracting $(1)$ from $(2)\times p$ gives $$ap^2+cp-a=0.$$

I do not know how to eliminate $p$ from the equations. I do not even know if this approach will solve it. And I have not been able yet to think of other approach.

If it is easy, then please give me some hint. Otherwise a solution, please!

$\endgroup$
5
  • 2
    $\begingroup$ I need my morning coffee before I try this seriously, but may be you can use reciprocal polynomials? The (complex) zeros of $f(x)=x^2+px+1$ are reciprocals of each other. This implies that $f(x)$ must be a common factor of both $g(x)=ax^5+bx^2+c$ as well as its reciprocal $\tilde{g}(x)=cx^5+bx^3+a$. This is because $g(\alpha)=0$ if and only if $\tilde{g}(1/\alpha)=0$. $\endgroup$ May 27 '18 at 7:15
  • $\begingroup$ The idea of reciprocal polynomials is not introduced yet, maybe introduced in some later chapter. And I am afraid you are talking about problem no. $41(ii)$, which I have been able to solve. @JyrkiLahtonen $\endgroup$ May 27 '18 at 7:21
  • 2
    $\begingroup$ @JyrkiLahtonen 's hint makes it fall out if you look at the fact $f|cg-a\tilde{g}$. $\endgroup$ May 27 '18 at 7:55
  • $\begingroup$ Feel free to flesh that ut to an answer @ancientmathematician ! $\endgroup$ May 27 '18 at 7:57
  • $\begingroup$ Thanks, Jyrki Lahtonen and ancientmathematician! Jyrki Lahtonen, now I have got your hint. And solved it. It was a fairly appropriate hint; and only my lack of proficiency failed me to catch it. $\endgroup$ May 27 '18 at 8:07
2
$\begingroup$

Denote $f_1(t) = at^4 - 3at^2 - bt + a$, $f_2(t) = at^3 - 2at - (b - c)$, then $f_1(p) = f_2(p) = 0$. Therefore, defining\begin{align*} f_3(t) &= t f_2(t) - f_1(t) = at^2 + ct - a,\\ f_4(t) &= a(tf_3(t) - f_2(t)) - c f_3(t) = (a^2 - c^2)t + ab,\\ f_5(t) &= (a^2 - c^2)^2 f_3(t) - a (f_4(t))^2 + 2a^2b f_4(t) - c(a^2 - c^2) f_4(t)\\ &= a(a^2 b^2 - (a^2 - c^2)(a^2 - c^2 + bc)), \end{align*} then$$ f_1(p) = f_2(p) = f_3(p) = f_4(p) = f_5(p) = 0 \Longrightarrow a(a^2 b^2 - (a^2 - c^2)(a^2 - c^2 + bc)) = 0, $$ and $a ≠ 0$ implies$$ (a^2 - c^2)(a^2 - c^2 + bc) = a^2 b^2. $$

$\endgroup$
1
  • $\begingroup$ I have not verified every step. But I have got the idea of your solution. It appears to be more of art than of science! Nice effort! $\endgroup$ May 27 '18 at 8:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.